2013 IEEE 13th International Conference on Data Mining Workshops 2013
DOI: 10.1109/icdmw.2013.131
|View full text |Cite
|
Sign up to set email alerts
|

A Semi-Supervised Learning Approach to Differential Privacy

Abstract: Motivated by the semi-supervised model in the data mining literature, we propose a model for differentiallyprivate learning in which private data is augmented by public data to achieve better accuracy. Our main result is a differentially private classifier with significantly improved accuracy compared to previous work. We experimentally demonstrate that such a classifier produces good prediction accuracies even in those situations where the amount of private data is fairly limited. This expands the range of us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…According to [36], a distance-recoverable protocol is not secure against malicious adversaries, which makes the method in [35] only suitable against a semi-honest adversary. Reference [37] assumed a scenario where additional nonprivate data are available and provided a learning model to improve the accuracy of a differential-private classifier using both private and non-private data. Reference [38] also proposed a semi-supervised learning method for differential privacy.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…According to [36], a distance-recoverable protocol is not secure against malicious adversaries, which makes the method in [35] only suitable against a semi-honest adversary. Reference [37] assumed a scenario where additional nonprivate data are available and provided a learning model to improve the accuracy of a differential-private classifier using both private and non-private data. Reference [38] also proposed a semi-supervised learning method for differential privacy.…”
Section: Related Workmentioning
confidence: 99%
“…Reference [38] also proposed a semi-supervised learning method for differential privacy. Like any other method for differential privacy, [37] and [38] focus on private information revealed by learning results and are not suitable for preserving data privacy against malicious collusion.…”
Section: Related Workmentioning
confidence: 99%
“…They observed that this algorithm performs better than the differentially private ID3 tree in terms of accuracy values even for small datasets. In 2013, they have proposed a variant of the differentially private random tree ensemble in [22]. In this study, a semi-supervised method which modifies the random decision tree approach to be used with the unlabelled data has been performed.…”
Section: Classification With Differential Privacymentioning
confidence: 99%
“…The utility-based partitioning is inspired by an observation that many DP machine learning algorithms (e.g. [5, 7, 9, 19]) have their performance related with n , ε for a dataset of n records with ε -DP. We give definition of utility-based partitioning below.…”
Section: Partitioning Mechanismsmentioning
confidence: 99%